Biomechanical effect of C5-C6 intervertebral disc degeneration on the human lower cervical spine (C3-C7): a finite element study. Issue 7 (19th May 2023) - Rahman, Waseem Ur; Jiang, Wei; Zhao, Fulin; Li, Zhijun; Wang, Guohua; Yang, Guanghui
Abstract: The biomechanical effects of intervertebral discs and facet joints degeneration on the cervical spine are essential to understanding the mechanisms of spinal disorders to improve pathological and clinical treatment. In this study, the biomechanical effects of a progressively degenerated C5-C6 segment on the human lower cervical spine are determined by a detailed simulation of intervertebral disc degeneration. A detailed asymmetric three-dimension intact finite element model was developed using computed tomography scan data of the human lower cervical spine (C3-C7). The intact finite element model was then modified at the C5-C6 segment to build three degenerated models, such as mild, moderate, and severe degeneration. The physiological compressive load 73.6 N, and moment 1 Nm were applied at the superior endplate of the vertebra C3, and the inferior endplate of the C7 vertebra was a constraint for all degrees of freedom. Range of motion, maximum von Mises stress in the annulus, intradiscal pressure, and facet joint force of the degenerated models were computed. With progressive degeneration in the C5-C6 segment, the range of motion of degenerated and normal segments decreases in all postures. Intradiscal pressure of the degenerated segment decreases but increases in normal segments of degenerated segment C5-C6, and facet joint forces increase at both degenerated and normal segments. This study emphasizes that the degenerated disc alters the degenerated and normal segments' motion and loading patterns. The abnormal increase in facet joint force in the degenerated models threatened to accelerate the degeneration in the normal segments.